2018
DOI: 10.1007/s00063-018-0402-5
|View full text |Cite
|
Sign up to set email alerts
|

Prophylaktische Anwendung von Tranexamsäure in der nichtkardialen Chirurgie

Abstract: Protease inhibitors such as TXA reduce perioperative blood loss and transfusion requirements in selected surgical fields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 92 publications
1
1
0
Order By: Relevance
“…These findings were comparable with our results. Strengthening the findings of present study WaskowskiJ et al, (2018) [16] in their review reported that TXA reduces perioperative blood loss and transfusion requirements in several randomized controlled trials. TA is beneficial in complex spine surgery and reconstructive surgery (e. g. craniosynostosis in children).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…These findings were comparable with our results. Strengthening the findings of present study WaskowskiJ et al, (2018) [16] in their review reported that TXA reduces perioperative blood loss and transfusion requirements in several randomized controlled trials. TA is beneficial in complex spine surgery and reconstructive surgery (e. g. craniosynostosis in children).…”
Section: Discussionsupporting
confidence: 74%
“…Single RCTs showed benefits of TXA in abdominal hysterectomy, open prostatectomy, liver surgery and actively bleeding trauma patients. (Waskowski J 2018) [16] WOMEN trial recruited 20 060 women aged 16 years and older with a clinical diagnosis of postpartum haemorrhage and reported that death due to bleeding was significantly reduced in women given tranexamic acid (155 [1•5%] of 10 036 patients vs 191 [1•9%] of 9985 in the placebo group and concluded that TA reduces death due to bleeding in women with post-partum haemorrhage with no adverse effects (WOMAN Trial Collaborators 2017) [17] . Use of topical hemostatics was higher among the control (77%) as compared to Cases (37%) (p=0.012) Contrary to present study reports of Topsoee MF et al, (2016) [11] showed that use of intraoperative topical hemostatics was not significantly different in both the groups which is in agreement to the finds of the ~ 97 ~ present study.…”
Section: Discussionmentioning
confidence: 99%